Integration of Andragogy and Pedagogy Approaches In Improving Student Learning Capabilities - Moh. Tito Ragil Dianang; Nurul Hidayat; Eka Firmansyah (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
Education in Phase D, specifically at the Junior High School (SMP) level, is a crucial transitional phase in student Development. This phase remains dominated by a pedagogical approach, namely, a teacher-centered learning process. Although the pedagogical approach is essential as a conceptual foundation and a discipline, it is less effective at developing student independence and learning capabilities. Thus, an integration of pedagogical and andragogical approaches is necessary to instill the principles of autonomy and relevance in adolescence. This research employed a qualitative case study approach, involving class VIII A students at SMP Negeri 1 Ngoro as the research participants. Data collection techniques included direct observation during the learning process, in-depth interviews, and analysis of student learning outcomes. Students' learning abilities were measured using three indicators: learning independence, critical thinking skills, and adaptability. Research shows that combining these two approaches successfully creates a more adaptive and transformative learning environment. Pedagogical principles provide a foundation for the structure and understanding of essential concepts, while andragogical elements, such as problem-based projects, reflective discussions, and the choice of assignments, enhance students' enthusiasm for learning and give them a sense of ownership over their learning process. There was a marked improvement in students' critical thinking skills when analyzing real-life situations and their ability to manage learning tasks independently. This study concludes that combining andragogical and pedagogical approaches for junior high school students is an effective model for strengthening learning abilities and helping them address learning challenges at higher levels of education and in everyday life.